Fungsi Pengawasan Badan Permusyawaratan Desa (BPD) dalam Pemberdayaan Masyarakat di Bidang Pariwisata di Desa Anakoli, Kecamatan Wolowae, Kabupaten Nagekeo - Sesilia Amata Ea; Boli Tonda Baso; Stefanus Triadmaja (International Forum of Researchers and Lecturers, 2026)
This study examines the supervisory role of the Village Consultative Body (BPD) in promoting community empowerment through tourism development in Anakoli Village, Wolowae District, Nagekeo Regency. The research is motivated by the underutilization of the village’s tourism potential, particularly Kota Jogo Beach, where inadequate supporting infrastructure, including shelters, public sanitation facilities, and organized spaces for local vendors, has limited tourism development and reduced opportunities for community economic participation. Effective supervision by the BPD is considered essential to ensure that tourism development programs not only focus on physical infrastructure but also strengthen community participation and local economic empowerment. This research adopted a qualitative descriptive approach. Data were obtained through field observations, in-depth interviews, and documentation involving the Chair of the BPD, the Village Head, and community representatives as key informants. The collected data were analyzed using data reduction, data presentation, and conclusion drawing to provide a comprehensive understanding of the implementation of the BPD’s supervisory function. The findings indicate that the BPD has performed its supervisory responsibilities through preventive, detective, and corrective supervision. Preventive supervision is conducted during planning and budgeting, detective supervision during program implementation, and corrective supervision through evaluation and recommendations for improvement. Nevertheless, the implementation remains less than optimal due to limited institutional capacity, weak coordination between the BPD and village government, low community participation, and the absence of sustainable tourism management. Strengthening the institutional capacity of the BPD, enhancing collaboration among stakeholders, and increasing community involvement are necessary to improve tourism-based empowerment, promote sustainable local development, and enhance community welfare in Anakoli Village.